A Supervisory and Control System for Indoor Lettuce Farming - Idzni, Sheikh Iqmal; Chia, Kim Seng (International Journal of Integrated Engineering, 2021)
The agriculture-based economy has undergone a significant transformation in the Malaysian economy where the agricultural sector has moved towards the status of an industrialized country rapidly. However, there are several challenges that threatens the ability to achieve this industrial status, namely the level of available technological advancements as well as the production efficiency. Malaysia has a tropical climate and monsoon seasons. With unpredictable weather conditions, it can affect the agricultural sector. Therefore, this study evaluates the performance of a proposed system in monitoring and controlling the variables that influence the growth of vegetables leading to optimal growth in indoor farming. The proposed system used various sensors to monitor temperature, humidity, and soil moisture, and to optimally control these parameters. Besides, a spectral light was used to replace the sunlight source so that indoor farming is feasible. The results show that the proposed system was able to accurately provide enough light that vegetables needed and to control the temperature better compared to a typical outdoor and traditional cultivation. Thus, the proposed system is promising to bring positive impact to the agricultural sector by providing a better environment conditions for growing vegetables.